IMPLEMENTATION OF PROJECT ORIENTED PROBLEM-BASED LEARNING (POPBL) MODEL INTEGRATED WITH STEM TO ENHANCE JUNIOR HIGH SCHOOL STUDENTS' SCIENCE CONCEPT MASTERY - Eliyawati Eliyawati; Yayan Sanjaya; A S Ramdani (JURNAL PENA SAINS, 2020)
The low ability of students to solve problems is in line with the low mastery of science concepts. In this study, Science, Technology, Engineering, and Mathematics (STEM) integrated Project Oriented Problem Based Learning (POPBL) learning models were implemented to improve the mastery of science concepts of junior high school students, especially on the topic of Environmental Pollution. The method used was a mixed-method. The STEM integrated STB learning model design framework consists of 3 stages: Onset Stage, Execution Stage, and Closure Stage. The concept of students is emphasized at the onset stage in the case study dissemination phase. In this phase, students analyze problems based on articles provided by the teacher. The more understanding the material, the more critical students will explore existing issues and find logical solutions to those problems. The results showed that there was a difference between the average pretest and posttest learning outcomes (t=-5,660; df = 53; Sig. (2-tailed) = 0,000). This indicates an increase in junior high school students' science concepts mastery after using the STEM integrated POPBL Learning Model. Improving students' mastery of concepts using a STEM integrated POPBL learning model is still in the low category with n-gain = 0.17. Although still in the low category, the POPBL learning model with the STEM approach can be optimized to improve students' mastery of concepts and skills on other science topics.